EDUKASI KEMARITIMAN SEJAK DINI MELALUI PENGENALAN HEWAN DAN TRANSPORTASI LAUT INDONESIA PADA SISWA MI FATHUL MA’ARIF DESA OLUHUTA KABUPATEN BONE BOLANGO - Sri Handayani; Kudus; Gamar Abdullah (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
The introduction of Indonesian marine animals and maritime transportation in elementary schools (Sekolah Dasar/SD and Madrasah Ibtidaiyah/MI) should be implemented from an early age to foster awareness of the preservation and sustainable management of Indonesia's marine natural resources. This study aimed to examine the understanding of lower-grade students regarding Indonesian marine animals and maritime transportation at MI Fathul Ma'arif, Oluhuta Village, Kabila Bone District, Bone Bolango Regency, Gorontalo Province, before and after the implementation of an educational intervention introducing Indonesian marine animals and maritime transportation. This study employed a quantitative approach using a one-group experimental research design. The study population consisted of lower-grade students from Grades 1, 2, and 3. A total of 24 students were selected through random sampling, with eight students representing each grade. The findings indicate that early maritime education through the introduction of Indonesian marine animals and maritime transportation effectively improved students' understanding and learning outcomes. This was demonstrated by an increase in the average test score from 51.667 on the pretest to 83.542 on the posttest. Furthermore, the number of students who achieved learning mastery increased from 2 students (8.3%) to 21 students (87.5%). The calculated N-Gain score of 0.66 indicates that the educational intervention was effective.